Trends in personalized nutrition - Galanakis, Charis M. (London ; San Diego, CA : Academic Press is an imprint of Elsevier, 2019)
Trends in Personalized Nutrition explores the topic of personalized nutrition from multiple angles, addressing everything from consumer acceptance, to policies and cognitive dissonance. Sections in the book cover epigenetics, nutrigenomics, predicting glycemic response, and metabolomics and the role of bacteria. In addition, the book explores diet, obesity and personalized nutrition for athletes, women, and infants and children, along with a section on the role of modern technology in the promotion of personalized nutrition. Nutritionists, food technologists, food chemists, new product developers, academics, and researchers and physicians working in the field of nutrition will find this to be a great reference.
Insights of personalized nutrition -- An introduction to personalized nutrition / Daniela Braconi, Vittoria Cicaloni, Ottavia Spiga And Annalisa Santucci -- Guidelines to evaluate the scientific validity for genotype-based dietary advice / Keith Anthony Grimaldi -- Personalized nutrition by predicting glycemic responses / Vaia Katsarou And Magdalini Tsolaki -- The role of bacteria in personalized nutrition / Sim K. Singhrao, Sarita Robinson and Alice Harding -- Cognitive dissonance in food and nutrition / Andy S. J. Ong -- Applications of personalized nutrition -- Trends, insights, and approaches to diet and obesity / I. Iglesia, P. De Miguel-Etayo, T. Battelino and L.A. Moreno -- Personalized nutrition for women, infants, and children / Elizabeth Wambui Kimani-Murage, Carolyn K. Nyamasege, Sandrine Mutoni, Teresia Macharia, Milka Wanjohi, Eva W. Kamande, Elizabeth Mwaniki, Peter G. Muriuki, Frederick Murunga Wekesah, Caroline Wainaina, Maurice Mutisya, and Taddese Alemu Zerflj - Modern technologies for personalized nutrition / Mike Boland, Fakhrul Alam, and John Bronlund -- Policy and commercialization of personalized nutrition -- Consumer acceptance of personalized nutrition / Zolt Szaky, Andr Feh And Marietta Kiss -- Personalized nutrition: making it happen / Barbara Stewart-Knox, Eileen R. Gibney, Mariette Abrahams, Audrey Rankin, Eleanor Bryant, Bruno M.P.M. Oliveira, and Rui Poinhos -- Personalized nutrition education to the adherence to dietary and physical activity recommendations / Liliana Guadalupe Gonzez-Rodruez, JosMiguel Perea-Schez, Pablo Veiga-Herreros, and {u2066}rica Peral Suarez -- Personalized expert recommendation systems for optimized nutrition / Chih-Han Chen and Christofer Toumazou.
Includes bibliographical references and index.
Keywords: Nutritional Physiological Phenomena -- Genetic; Functional Food; Precision Medicine; Nutrigenomics